The price of violence: Consequences of violent crime in Sweden - Petra Ornstein (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2017)
The connection between violence victimization and long term ill-health is well documented, but evidence is lacking on the causal effects of victimization beyond the time of the immediate injury. The aim of this study is to identify and estimate the longer term consequences of interpersonal violence on victims. Using rich administrative population data for Sweden, I compare individuals who visited a hospital in the years 1998 to 2002 due to assault with individuals who did not experience assault, but who were statistically indistinguishable from the cases of interest in the four years prior to the incident. The results suggest that violent crime has large and persistent effects on mortality, suicide, earnings, work status, disposable income, as well as on the number of days on sick leave. Specifically, an assault leading to a hospital visit is estimated to convey losses amounting to 1.4 million SEK per victimized woman and 1.5 million SEK per victimized man, whereof more than 80 percent result from excess mortality. Estimates on socio-economic outcomes show robustness against selection on unobserved characteristics. Estimates on mortality and suicides are very robust.
Keywords: I12; I14; J12; J17; K42; 330; suicide; mortality; domestic abuse; value of statistical life; violent crime